Gamifying Academic Integrity: An Inclusive, Interactive Model for Teaching Ethical Academic Practice in Higher Education - Bakogiannis, Angelos; Papavasiliou, Evie (Innovations in Pedagogy and Technology, 2026)
Academic integrity remains a key challenge in higher education. At Teesside University, increasing cases of plagiarism, collusion, and contract cheating highlighted the need for more engaging and educationally grounded interventions. In response, the English Language Centre (ELC) designed and delivered a two-part initiative integrating gamification and inclusive pedagogy to reframe integrity as a participatory academic literacy rather than a compliance exercise. The programme combined a large interactive lecture introducing core integrity principles with a practical workshop developing paraphrasing, quoting, and summarising skills. Kahoot! was embedded throughout as a gamified learning tool that fostered participation, inclusivity, and real-time feedback. Across 26 Embedded Academic Literacies (EAL) sessions, the initiative engaged 620 students from all five Schools. Anonymous feedback showed that over 90% of participants found the sessions useful and reported increased understanding, frequently describing them as “informative,” “interactive,” “engaging,” and “fun.” Participants also demonstrated a 25% reduction in average similarity scores compared with previous cohorts, indicating measurable improvement in integrity-related practices. Staff observed that engagement and responsiveness declined when institutional access to Kahoot! was temporarily lost, reinforcing its pedagogical value. This short communication presents a case study of this innovation, drawing on routine anonymous feedback and staff reflections to illustrate how gamification can enhance academic integrity education in inclusive, diverse settings. The findings suggest that framing integrity as an interactive literacy, supported by game-based participation, can increase engagement, confidence, and ethical academic practice across disciplines.